Evaluation of the Internal Management System in Supporting Administrative Efficiency at CV Cahaya Lestari Sukses - M, Melvina; Dewi, Sari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to evaluate the internal management system of Cahaya Lestari Sukses Company in order to improve administrative efficiency by implementing Standard Operating Procedures (SOP) based on Total Quality Management (TQM). The main issues found were lack of order in recording purchases, sales, project cost control, and poor documentation in the human resources process, which led to financial reporting errors and operational data inconsistencies. The research used a qualitative method through observation, semi-structured interviews, and documentation to gain a comprehensive understanding of the company's operational conditions. The results showed that applying SOP in eight key areas—purchase of raw materials, sales and project contracts, finance and accounting, project cost control, internal service and communication, recruitment and selection, occupational health and safety (K3), and payroll—successfully improved administrative order, clarity in workflow, accuracy in record-keeping, effectiveness in internal communication, and cost control. The SOP training provided also strengthened the consistency of procedure implementation and improved employees' understanding of their respective tasks. The study concludes that integrating SOP based on TQM can significantly improve business processes and provide a more measurable operational foundation for construction companies. It is recommended that the company conduct regular SOP evaluations and ensure routine training to maintain the continuity of operational quality.